PEMENUHAN HAK-HAK TENAGA KERJA PEREMPUAN OLEH PERUSAHAAN (STUDI TERHADAP HAK-HAK PEREMPUAN YANG BEKERJA PADA APOTEK DI KOTA PEKANBARU) - Ananda, Ariestia Ayu; Hendra, Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
In line with the growth speed of the Indonesian population, the labor and the labor force will increase. One of those opportunities or employment opportunities offered to people who have specific knowledge in the pharmaceutical field is to work in a pharmacy .. The purpose of this thesis namely; First, the legal protection of women workers who work in a pharmacy in the city of Pekanbaru, Second, the fulfillment of the rights of women workers who work in a pharmacy, Third, efforts to provide protection to child asylum seekers in Indonesia.This type of research is a kind of sociological research. This research was conducted at the Department of Labor and the Pekanbaru city pharmacies in the city of Pekanbaru. While the overall population and the sample is related to the issues examined in this study. The data used are primary data and secondary data and data collection techniques using observation (observation), interviews, questionnaires, and literature.Technical analysis of qualitative, inductive inference techniques. From the research, there are three main issues that can be inferred. First, the legal protection for women workers has been regulated in the Law on Employment and international conventions that have been ratified to Indonesian law. Second, the fulfillment of the rights of women workers who work in pharmacies are still many unmet, many rights are supposed to get but do not they get. Third, efforts made by the government for the rights of women workers to conduct routine surveillance kesetiap firms in the city of Pekanbaru and if at the time of Manpower conduct surveillance at the pharmacy. Suggestions author, Manpower as a governing body would be expected to increase the number of its members in order to provide optimal protection against the workers, especially women workers, and the need to socialize about Manpower Employment Act against the workers, so that workers can determine the rights to be acquired and obligations.Keywords: Fulfillment Rights - Women Workers - Pharmacy Pekanbaru